Influência do tipo de impressão, do pós processamento e do tipo de resina na resistência à flexão e na estabilidade dimensional de resinas impressas - Moreira, Fernanda Gurgel de Gois (2022)
Objective: To evaluate the influence of different post-processing protocols and the type of 3D printing of different printed resins on the three-point bending strength () and dimensional stability. Methodology: A bar was modeled (26 x 2.2 x 2.2mm) on Mishmixer software and a STL file was obtained, the it was exported to the 3D printer software SLA (Forms 2/Formslab) and LCD (FlashForge Photo 6.0/ FlashForge). Then, 45 bars of each type of resin (Pr - Provisional/Cosmos Temp, Yller; Pl - Occlusal Plate/Cosmos Splint, Yller; Mo – Models/ Cosmos Model, Yller) were printed by each printing system (SLA and LCD). After printing, the bars of each type of resin were cleaned with isopropyl alcohol and randomly divided (n=15) according to factors: “Post-processing protocol” Control (C: without post-processing); Ultraviolet Light (UV: 15 min in Anycubic Wash and Cure Plus, Anycubic) and Microwave (M: 15 min in microwave oven/1,400W). Thein, the bars were submitted to the  test (100KgF, 1mm/min) and data (MPa) analyzed with 2-way ANOVA and Tukey (5%). Complementary analyzes of dimensional stability (analyzed by paired T tests and 2-way ANOVA) and SEM of surfaces and fractures were also performed. Results: For the flexural strength of the model resin, 2-way ANOVA indicated that the factors "Printer" (p<0.0001) and "Post processing" (p<0.0001) showed statistical significance. The SLAMUV (33.80±4.82AMPa) and LCDMUV (35.93±4.47AMPa) groups presented higher  values, being statistically superior to the groups without post-processing and microwave-processed powders. For the provisional resin groups, 2-way ANOVA revealed that the factors "Printer" (p=0.0044) and "Post processing" (p<0.0001) were statistically significant. The LCDPUV group showed the highest flexural strength (52.06±12.40AMPa), followed by SLAPUV (42.86±2.09BMPa) and SLAPMO (26.73±5.48CMPa). For the plate groups, 2-way ANOVA showed that the factors "Printer" (p<0.0001) and "Post processing" (p<0.0001) were statistically significant. The LCDPLUV group (91.46±12.33AMPa) presented the highest flexural strength value, being statistically superior to the other groups. For dimensional stability, on the template resin, the T-test for paired samples demonstrated that only the SLA printed samples showed a significant change in width and thickness after post-processing methods. For length, only the samples post-cured in ultraviolet light had significant changes (p<0.05). Regarding the resin for plates, the SLAPlUV group presented greater variations in the three dimensions analyzed (width: -55.60Aµm; thickness: -12.80Aµm; length: -93.73Aµm), and for presenting negative data, we suggest material expansion. Regarding the resin for provisional, in all dimensions studied, the LCDProv-UV group showed greater dimensional changes (width: 31.46Aµm; thickness: - 28.40Bµm; length: -86.53Aµm), while the LCDProv-MO group presented minor changes (width: -7.20 Bµm; thickness: -4.40 Aµm; length: 18.00 Bµm). Conclusion: It could be concluded that the post processing in ultraviolet light promoted the best values of flexural strength for all types of resins evaluated, being the LCD printing technique the one that presented the best values of () when associated with post processing in ultraviolet light, regardless of the type of resin. Dimensional stability is associated with the type of resin and post-processing used.